2020
DOI: 10.1111/anu.13197
|View full text |Cite
|
Sign up to set email alerts
|

Dietary tributyrin modifies intestinal function by altering morphology, gene expression and microbiota profile in common carp ( Cyprinus carpio ) fed all‐plant diets

Abstract: Fishmeal (FM) and fish oil (FO), which are recognized as the high-quality aquatic feed ingredients with balanced essential amino acid (EAA) profile, essential fatty acid (EFA, such as docosahexaenoic acid or DHA and eicosapentaenoic acid or EPA), and excellent palatability and digestibility, are widely applied to the diet of most farm fish (Dawood, 2020). With the aquaculture demand for FM and FO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 66 publications
4
24
1
Order By: Relevance
“…The present study showed that the addition of TB to high CRM diets tended to improve the growth performance of grass carp so that the addition of 1000 mg/kg TB presented the same growth as compared with the PC group. These results are consistent with results obtained from common carp (Xie et al, 2021) and shrimp (Liu et al, 2021). This result may be due to the fact that TB can improve the intestinal health of fish.…”
Section: Ta B L Esupporting
confidence: 92%
See 2 more Smart Citations
“…The present study showed that the addition of TB to high CRM diets tended to improve the growth performance of grass carp so that the addition of 1000 mg/kg TB presented the same growth as compared with the PC group. These results are consistent with results obtained from common carp (Xie et al, 2021) and shrimp (Liu et al, 2021). This result may be due to the fact that TB can improve the intestinal health of fish.…”
Section: Ta B L Esupporting
confidence: 92%
“…This result may be due to the fact that TB can improve the intestinal health of fish. Studies have shown that the intestinal digestive capacity by the regulation of growth and development is closely related to intestinal villus length in common carp (Xie et al, 2021). Villus length and muscular thickness are important indicators of the efficiency of intestinal digestion and absorption (Pirarat et al, 2011).…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that supplementation of tributyrin can significantly improve the tight junctions in the distal intestine of hybrid grouper. Dietary 0.05%-0.40% tributyrin to feed promoted tight junctions in the distal intestine of common carp by upregulating the expression of occludin and ZO-1 (Xie et al, 2020). It can also attenuate chronic alcohol overdose induced intestinal barrier damage in mice by upregulating the protein expression of claudin3, occludin and ZO-1 (Cresci et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Chi square values of each comparison objects are 14.02 for FM versus S00, 1.259 for S00 versus S02, 6.615 for S00 versus S04, 7.423 for S00 versus S08, 38.75 for S00 versus S16, 33.94 for S00 versus S32 and 69.52 for all the six low fishmeal groups (S00 to S32) model was developed, and the results showed that hybrid grouper obtained the maximum SGR at a tributyrin level of 0.186% in feed percentage. In common carp (Cyprinus carpio), supplementation of whole plant protein with 0.2%-0.4% tributyrin was effective in increasing SGR and decreasing FCR of common carp whilst also significantly improving HSI and ISI(Xie et al, 2020). The addition of 0.2% tributyrin to the diet of white shrimp(Litopenaeus vannamei)…”
mentioning
confidence: 99%